2017
DOI: 10.1148/radiol.2017162321
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer: Diffusion-weighted MR Imaging for Detection and Assessment of Aggressiveness—Comparison between Conventional and Kurtosis Models

Abstract: Purpose To compare standard diffusion-weighted (DW) imaging and diffusion kurtosis (DK) imaging for prostate cancer (PC) detection and characterization in a large patient cohort, with attention to the potential added value of DK imaging. Materials and Methods This retrospective institutional review board-approved study received a waiver of informed consent. Two hundred eighty-five patients with PC underwent 3.0-T phased-array coil prostate magnetic resonance (MR) imaging, including a DK imaging sequence (b val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 27 publications
7
40
1
Order By: Relevance
“…They showed an excellent performance for ADC (AUC, 0.93; sensitivity, 78.5%; specificity, 95.7%), which was even further improved using diffusion kurtosis imaging (AUC, 0.98; sensitivity, 93.3%; specificity, 95.7%). However, in a recent study including 285 patients with PCa, the same group found no clear benefit for diffusion kurtosis imaging (AUC, 0.90) in comparison to standard DWI (AUC, 0.92) . In an ex vivo study, McGrath et al found no significant difference in ADCs between PCa and healthy tissue, although ADC values tended to be lower in PCa .…”
Section: Discussionmentioning
confidence: 94%
“…They showed an excellent performance for ADC (AUC, 0.93; sensitivity, 78.5%; specificity, 95.7%), which was even further improved using diffusion kurtosis imaging (AUC, 0.98; sensitivity, 93.3%; specificity, 95.7%). However, in a recent study including 285 patients with PCa, the same group found no clear benefit for diffusion kurtosis imaging (AUC, 0.90) in comparison to standard DWI (AUC, 0.92) . In an ex vivo study, McGrath et al found no significant difference in ADCs between PCa and healthy tissue, although ADC values tended to be lower in PCa .…”
Section: Discussionmentioning
confidence: 94%
“…Indeed, our simulations in this study indicated uncorrected magnitude data can result in a ~7% increase of true K values in NPZ tissue. This is concerning and may account for the mixed results from earlier studies that compare DKI with DWI for PCa, where often no noise‐correction method is performed at all. Here, we have investigated a real‐data reconstruction approach to noise bias removal from DKI in the prostate.…”
Section: Resultsmentioning
confidence: 99%
“…One such expanded model is diffusional kurtosis imaging (DKI), which provides an estimate of the apparent diffusional kurtosis ( K ): a dimensionless parameter that quantifies the degree of non‐Gaussian diffusion. Since the first DKI studies, the technique has been applied extensively in neuroimaging and other studies have demonstrated feasibility for body applications, including PCa . Several investigations have compared DKI with standard DWI in PCa, with disagreement over whether DKI brings additional value compared to standard DWI or not .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This goes along with the results of Roethke et al (67) who did not find a significant benefit of DKI compared with ADC as they used a separate DWI sequence with shorter echo times and lower b -values to calculate ADC maps. Recently, a study comparing the value of DW-MRI and DKI for PCa detection and characterization included a large population of 255 patients to evaluate the potential value of DKI (70). The authors found that ADC and DKI were highly correlated and had a similar diagnostic performance, but did not show a clear added value of DKI compared with standard DW-MRI.…”
Section: Advances In Dwi Of the Prostatementioning
confidence: 99%